STUDI PERBAIKAN SALURAN SEKUNDER DAERAH KARANG AGUNG HILIR DI DESA SR AGUNG - Aditya Wicaksono; Firdaus Firdaus (Rang Teknik Journal, 2026)
The success of agriculture in tidal swamp areas significantly depends on the sustainability of irrigation infrastructure. SR Agung Village in Karang Agung Hilir, Banyuasin Regency, is a transmigration area suffering from the degradation of secondary irrigation channels due to sedimentation, embankment damage, and uncontrolled vegetation growth. This study aims to comprehensively describe the existing conditions of the secondary channel and evaluate the effectiveness of the rehabilitation efforts undertaken. The research employed a qualitative descriptive method with data collection through field observations, interviews with project stakeholders, documentation review, and active participation. The results revealed damage including embankment cracks up to 30 cm deep, sediment buildup reducing channel capacity by 60%, and aquatic vegetation covering 70–80% of the water surface. Rehabilitation strategies involved embankment reinforcement using geotextiles and crack injection, sediment dredging, and integrated vegetation control. Technical design followed the Detail Engineering Design (DED) approach, incorporating topographic, hydraulic, and geotechnical data. Rehabilitation outcomes showed a 40% increase in flow capacity and a 25% reduction in water loss. In conclusion, the rehabilitation significantly improved irrigation efficiency, agricultural productivity, and local food security. It is recommended to implement routine maintenance programs using digital technology and encourage community involvement through Water User Associations to ensure long-term infrastructure sustainability. Keywords: Secondary Irrigation, Irrigation Rehabilitation, Swamp Channel, SR Agung Village, Water Efficiency